The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1759-7714.12883
|View full text |Cite
|
Sign up to set email alerts
|

Blocking FGFR4 exerts distinct anti‐tumorigenic effects in esophageal squamous cell carcinoma

Abstract: BackgroundThe FGFR family can be activated by FGFs and plays important roles in regulating cell growth, differentiation, migration, and angiogenesis. Recent studies have suggested that FGFR4 could regulate several processes, including tumor progression. Esophageal squamous cell carcinoma (ESCC) is a malignancy with high global occurrence. However, the molecule mechanism and the potential roles of FGFR4 in ESCC remain unknown.MethodsImmunohistochemistry and Western blotting were used to detect FGFR4 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…EMT has been widely accepted as a critical factor in tumor initiation and metastasis 9,26,35,37 . Its key regulatory role in invasion and metastasis has been reported in many human cancers including ESCC 25,28,34,38,39 . EMT has also been connected to the induction of immunosuppression and drug resistance 27,40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT has been widely accepted as a critical factor in tumor initiation and metastasis 9,26,35,37 . Its key regulatory role in invasion and metastasis has been reported in many human cancers including ESCC 25,28,34,38,39 . EMT has also been connected to the induction of immunosuppression and drug resistance 27,40 .…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH (1:5000, Proteintech) was used as control. The results were quantified by Quantity One software (Bio‐Rad) 11,26,29,34 …”
Section: Migration and Invasionmentioning
confidence: 99%
“…Overexpression of FGFR4 predict metastasis and poor survival outcome in various cancers [ 56–58 ]. Blocking FGFR4 significantly suppresses the cancer and indicates that FGFR4 is a potential target for the cancer treatment [ 59 ]. Polymorphisms in the FGFR4 rs351855 (Gly 388 Arg) polymorphism, is positioned in the transmembrane domain of the EGFR4.…”
Section: Discussionmentioning
confidence: 99%
“…These experimental results make FGFR4 an interesting therapeutic target, the safety of which has already been proven in clinical trials in cardiovascular diseases (reported at www.clinicaltrials.gov : NCT02476019). In addition, FGFR4 blockade is currently used in oncology trials as neoadjuvant chemotherapy to improve patients’ response, since it has a beneficial anti-angiogenic effect ( Xin et al, 2018 ; Gluz et al, 2020 ).…”
Section: Strategies To Avoid Deleterious Fgf-23 Effects On the Heartmentioning
confidence: 99%